Alkali-facilitated deep eutectic solvent for effective bamboo saccharification. (January 2023) - Liu, Xuze; Cheng, Jinyuan; Huang, Chen; Wang, Jia; Fang, Guigan; Shen, Kuizhong; Meng, Xianzhi; Ragauskas, Arthur J.
Graphic abstract: Highlights: A novel alkaline DES using Na2 S as the reinforcer was proposed in this study. The alkaline DES showed excellent delignification and carbohydrates preservation. The alkaline DES realized the full utilization of biomass. Abstract: Herein, a Na2 S promoted deep eutectic solvent (DES) was established to reduce the natural recalcitrance of moso bamboo (MB) and improve the subsequent enzymatic saccharification. It was found that the addition of Na2 S (Choline chloride/Ethylene glycol/Na2 S) dramatically promoted the deconstructions of lignin with highest removal of 74.67 %, but at the same time preserved glucan and hemicellulose to the maximum extent. With the fractionation, the enzymatic saccharification yield of pretreated MB can reach 100 % under the pretreatment condition of 140 °C, and lignin could be readily recovered with a high yield of 81.47 %. The proposed DES is superior to normal alkaline DES in terms of the higher lignin removal and recovery yield, carbohydrate preservation and enzymatic digestibility, which indicated Na2 S as a novel and powerful reinforcer enhancing the DES fractionation efficiency.